PELATIHAN PEMANDU EKOWISATA DAN PEMANFAATAN HASIL HUTAN BUKAN KAYU PADA KUPS. BUKIT LONA KOTA TIDORE KEPULAUAN - Asiah Salatalohy; Aqshan Shadikin Nurdin (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
This activity aims to provide training for ecotourism guides and the use of non-timber forest products at the Bukit Lona Social Forestry Group (KUPS), Lada Ake Environment, Jaya Village, North Tidore District, Tidore Islands City with 10 participants. The method of implementing the activity is (1) direct face-to-face/lecture (2) a demonstration of making souvenirs using the method of directing instructions to partners. The success of this activity was shown by the enthusiasm of partners in providing positive responses to understanding the material provided. Likewise in the manufacture of souvenir products. All materials used are materials that are widely available around the training location, so they will provide better results in the utilization of potential non-timber forest products in the local area. The result of this training is an increase in participants' knowledge in ecotourism guide activities as well as souvenir products from non-timber forest products in the form of doll statues and brooches.